COBA-Cohort: a prospective cohort of HIV-negative men who have sex with men, attending community-based HIV testing services in five European countries (a study protocol). Issue 7 (13th July 2016) - Lorente, Nicolas; Fernàndez-López, Laura; Fuertes, Ricardo; Rojas Castro, Daniela; Pichon, François; Cigan, Bojan; Chanos, Sophocles; Meireles, Paula; Lucas, Raquel; Morel, Stéphane; Slaaen Kaye, Per; Agustí, Cristina; et al.
Abstract : Introduction: Community-based voluntary counselling and testing (CBVCT) services for men who have sex with men (MSM) can reach those most-at-risk and provide an environment for gay men that is likely to be non-stigmatising. Longitudinal data on the behaviour of HIV-negative MSM are scarce in Europe. The aim of this protocol, developed during the Euro HIV Early Diagnosis And Treatment (EDAT) project, is to implement a multicentre community-based cohort of HIV-negative MSM attending 15 CBVCT services in 5 European countries. Research objectives: (1) To describe the patterns of CBVCT use, (2) to estimate HIV incidence, and to identify determinants of (3) HIV seroconversion and (4) HIV and/or sexually transmitted infection (STI) test-seeking behaviour. Methods and analysis: All MSM aged 18 years or over and who had a negative HIV test result are invited to participate in the COmmunity-BAsed Cohort (COBA-Cohort). Study enrolment started in February 2015, and is due to continue for at least 12 months at each study site. Follow-up frequency depends on the testing recommendations in each country (at least 1 test per year). Sociodemographic data are collected at baseline; baseline and follow-up questionnaires both gather data on attitudes and perceptions, discrimination, HIV/STI testing history, sexual behaviour, condom use, and pre- and post-exposure prophylaxis. Descriptive, exploratory and multivariate analyses will be performed to address the main research objectives of this study, using appropriate statistical tests and models. These analyses will be performed on the whole cohort data and stratified by study site or country. Ethics and dissemination: The study was approved by the Public Health authorities of each country where the study is being implemented. Findings from the COBA-Cohort study will be summarised in a report to the European Commission, and in leaflets to be distributed to study participants. Articles and conference abstracts will be submitted to peer-reviewed journals and conferences.